Изменение образа жизни - высокоэффективный инструмент в арсенале терапевта. Часть 1 - Н. И. Волкова; И. С. Джериева (SINAPS LLC, 2011)
The rapid increase of metabolic disorders (MD) associated with transformation of the population lifestyle is one of the main reasons for cardiovascular complications (CVC), which lead to disability in some cases and deaths in the other. This article discusses the main modern methods of correction known risk factors for CVC and provides concepts for new risk factors of MD to draw attention to the need for lifestyle changes as a method of prevention and treatment of MD, including metabolic syndrome, and CVC.